2016
DOI: 10.1039/c6ra23261b
|View full text |Cite
|
Sign up to set email alerts
|

Materials for aqueous sodium-ion batteries: cation mobility in a zinc hexacyanoferrate electrode

Abstract: The coordination polymer Zn3Na2[FeII(CN)6]2 has an open porous framework that is stable in acidic and neutral aqueous solutions and appears to be an attractive solid for investigation as a material for sodium ion-based batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 31 publications
3
39
0
1
Order By: Relevance
“…The net effect is an overlapping for the electron clouds of the involved metals (M, T). This explains the attractive properties of this family of materials as prototype of molecular magnets, which have been widely studied in the last decades The presence of two redox centers linked through the CN bridge and for some compositions also of an exchangeable alkali metal (A), has stimulated their study as materials for new generation of batteries, in electrochemical sensors, environmental remediation,, and for health care . For certain combinations of metals, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The net effect is an overlapping for the electron clouds of the involved metals (M, T). This explains the attractive properties of this family of materials as prototype of molecular magnets, which have been widely studied in the last decades The presence of two redox centers linked through the CN bridge and for some compositions also of an exchangeable alkali metal (A), has stimulated their study as materials for new generation of batteries, in electrochemical sensors, environmental remediation,, and for health care . For certain combinations of metals, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…for new generation of batteries, [4][5][6] in electrochemical sensors, [7][8][9] environmental remediation, [10,11] and for health care. [12] For certain combinations of metals, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, two dimensional materials such as layered MoS 2 , MoSe 2 , TiS 2 , and MXene, are recently explored as Na‐ion intercalative pseudocapacitive materials ,. In this scenario, metal organic framework mimicking metal hexacyanoferrate have been studied as electrode materials for Na‐ion batteries and capacitors ,. The metal hexacyanoferrate possess the Prussian blue crystal structure which can intercalate variety of ions such as Li + , and Na + during electrochemical charge‐discharge cycles .…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] In this scenario, metal organic framework mimicking metal hexacyanoferrate have been studied as electrode materials for Na-ion batteries and capacitors. [14,15] The metal hexacyanoferrate possess the Prussian blue crystal structure which can intercalate variety of ions such as Li + , and Na + during electrochemical charge-discharge cycles. [16] In a recent work, M. Wan et al demonstrated the superior electrochemical activity of core-shell structured Fe-HCF@Ni-HCF electrodes for sodium ion storage for Na-ion batteries.…”
Section: Introductionmentioning
confidence: 99%